Tertullian's preface to Marcion's Gospel - Vinzent, Markus 1959- (Studia patristica. Supplement, 2016)
Over the past few years, scholarship has taken a new interest in the study of Marcion and particularly in his Gospel. Most recently several attempts have been made at reconstructing this Gospel, and its role in the Synoptic question is being discussed. One of the most detailed and crucial information that we possess derives from Tertullian's preface to Marcion's Gospel and his 'Antitheses' with which Marcion himself introduced and defended his Gospel against earlier misuses. The present monograph first looks at Tertullian's ways of prefacing his works to then move to his preface of his antimarcionite writings, especially 'Adversus Marcionem', to then give the text, translation and a close reading and interpretation of his introduction to the 'Antitheses' and Marcion's Gospel in the extended preface to book IV of 'Adversus Marcionem'. 0As a result, the reader will get a better understanding of both Tertullian's literary response to Marcion and Marcion's 'Antitheses' and his Gospel, but also gain glimpses of what despite all the rhetoric historically might have provoked Tertullian's response, namely more intellectual proximity between the two interlocutors than the battle on the surface would intimate